TINDAK TUTUR ILOKUSI DEKLARATIF BAHASA JEPANG DALAM DRAMA BEAUTIFUL RAIN - Istaqori, Fa?ni; Aibonotika, Arza; Budiani, Dini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The topic discussed in the paper is about the type of declarative illocutionary speech acts based on theories from Searle (1969) and Leech (1993) that found in drama Beautiful Rain. This research attempts to describe kinds of Japanese language declarative illocutionary speech act drama Beautiful Rain and describe the characteristic of declarative illocutionary speech act. The kind of this research is qualitative descriptive research and to find description of character’s speech in drama Beautiful Rain. The method of collecting the data used in this research is uninvolved conversation observation technique. Those method used to find the complete data of declarative illocutionary speech act. The result of this research finds 48 speech consist thing eight kind declarative illocutionary speech act: 14 declarative illocutionary speech act ‘decision’, 8 declarative illocutionary speech act ‘validity’, 4 declarative illocutionary speech act ‘naming’, 5 declarative illocutionary speech act ‘canceling’, 8 declarative illocutionary speech act ‘prohibitive’, 2 declarative illocutionary speech act ‘forgiving’, 3 declarative illocutionary speech act ‘helping’, and 4 declarative illocutionary speech act ‘permitting’. The analysis also find the specific characteristic of declarative illocutionary speech act: performative declarative speech, physical a declarative speech, and each declarative speech has the significant meaning based on the context.Key Words: Japanese Language Declarative Illocutionary Speech Act, Type of DeclarativeIllocutionary, Pragmatic Meaning